Residual strains in AA2024/AlSiCp composite linear friction welds - Jun, T; Rotundo, F; Song, X; Ceschini, L; Korsunsky, A (Elsevier, 2010)
The present paper is devoted to the study of residual strains in AA2024/AlSiCp linear friction welds, using a novel approach based on eigenstrain. Synchrotron X-ray and neutron diffraction were used to measure the interplanar lattice spacing in the welds and deduce the residual elastic strains as a function of the distance from the bond line. The limited experimental datasets were combined with eigenstrain-based FE modelling in order to reconstruct the complete strain states in the entire components. The reconstructed strain distributions were validated with further experiments, indicating good agreement for both cases. It was found that the approach based on eigenstrain is a powerful basis for reconstructing full-field residual strain/stress distributions in engineering structures.